2013
DOI: 10.1016/j.str.2013.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Gating of Pentameric Ligand-Gated Ion Channels: Structural Insights and Ambiguities

Abstract: Pentameric ligand-gated ion channels (pLGICs) mediate fast synaptic communication by converting chemical signals into an electrical response. Recently solved agonist-bound and agonist-free structures greatly extend our understanding of these complex molecular machines. A key challenge to a full description of function, however, is the ability to unequivocally relate determined structures to the canonical resting, open, and desensitized states. Here, we review current understanding of pLGIC structure, with a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 141 publications
(216 reference statements)
8
101
0
Order By: Relevance
“…Significantly, agonist binding does not lead to a widening of the channel pore in ELIC, even with mutants that show no propensity to undergo desensitization (54,55). Although wild type ELIC appears less sensitive to detergent than the nAChR, the absence of aromatic residues in the post-M4 region may weaken post-M4-M1/M3 interactions so that detergent solubilization leads to a non-functional conformation (15), as does reconstitution into the minimal PC membranes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Significantly, agonist binding does not lead to a widening of the channel pore in ELIC, even with mutants that show no propensity to undergo desensitization (54,55). Although wild type ELIC appears less sensitive to detergent than the nAChR, the absence of aromatic residues in the post-M4 region may weaken post-M4-M1/M3 interactions so that detergent solubilization leads to a non-functional conformation (15), as does reconstitution into the minimal PC membranes.…”
Section: Discussionmentioning
confidence: 96%
“…Lipid-dependent mechanisms for "awakening" uncoupled nAChRs have been identified and could play a role modulating synaptic communication (14). The lipid-dependent uncoupled conformation may also be germane to the interpretation of crystal structures of detergent-solubilized pLGICs (15). Lipids may exert their effects on nAChR function by interacting with interstitial sites between ␣-helices in the transmembrane domain (16,17) or by interacting with the lipid-protein interface (11,16,18,19).…”
mentioning
confidence: 99%
“…Several factors may contribute to the observed structural differences between these channels (17,61). The structural models of nAChR in the unliganded and liganded conformations are based on 4-and 6-Å resolution data, respectively (1,62).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no movement of the porelining M2 α-helices was detected with mutants that prolong channel opening and exhibit no propensity to desensitize. It has been suggested that the ELIC structures reflect a conformation that is refractory to agonist binding [121] -i.e., a conformation that is functionally equivalent to the lipid-dependent uncoupled state of the Torpedo nAChR [122]. Significantly, the ELIC structures exhibit multiple proposed features of the uncoupled nAChR ( Figs.…”
Section: Insight From Crystal Structures Of Prokaryotic Plgicsmentioning
confidence: 94%